2003
DOI: 10.2190/adan-3g4a-t3a5-qp4t
|View full text |Cite
|
Sign up to set email alerts
|

Imminent Concerns Of Filial Caregivers Reporting Recent Experiences Of Crisis

Abstract: The purpose of this descriptive study was to generate information about imminent concerns of adult children that could serve as initial context for development of a meaningful framework for coping with an ongoing parent care situation. Ninety-two adult children pre-selected for self-reports of crisis were interviewed about their concerns and goals for caregiving and asked to discuss experiences of crisis in the previous six months of caregiving. Key issues pertaining to their experiences were extracted from no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…40,41 Publications describe strategies for sampling, [42][43][44][45] analyzing, reporting, [45][46][47][48][49] and combining qualitative and quantitative methods 50 ; and a growing body of health care research reports fi ndings from studies using in-depth interviews, [51][52][53][54] focus groups, [55][56][57] observation, [58][59][60] and a range of mixed-methods designs. [61][62][63] As part of a project to evaluate health care improvements, we identifi ed a need to help health care researchers, particularly those with limited experience in qualitative research, evaluate and understand qualitative methodologies.…”
Section: Crit Er Ia F or Qu A L Itat Iv E R Ese A Rchmentioning
confidence: 99%
“…40,41 Publications describe strategies for sampling, [42][43][44][45] analyzing, reporting, [45][46][47][48][49] and combining qualitative and quantitative methods 50 ; and a growing body of health care research reports fi ndings from studies using in-depth interviews, [51][52][53][54] focus groups, [55][56][57] observation, [58][59][60] and a range of mixed-methods designs. [61][62][63] As part of a project to evaluate health care improvements, we identifi ed a need to help health care researchers, particularly those with limited experience in qualitative research, evaluate and understand qualitative methodologies.…”
Section: Crit Er Ia F or Qu A L Itat Iv E R Ese A Rchmentioning
confidence: 99%
“…By emphasizing the psychological benefits, such as emotional support, and identifying concrete examples in which aging parents can assist their adult children, aging parents' self-worth could be enhanced and their frustration reduced. England and Tripp-Reimer (2003) conducted a descriptive study to produce information regarding imminent concerns of caregivers and a framework for coping with long-term care of an aging parent. The researchers sought to identify issues related to adult children's experiences of crisis in caregiving during the last 6 months and to link issues related to experiences of crisis with adult children's potential to implement viable parent care.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The issues highlighted by the participants were categorized in five domains: (a) significant life and death; (b) family relational burden, which encompassed filial, sibling, and marital strains as well as disabilities and limited resources; (c) early childhood experiences from family of origin, which included child abuse, poverty, and circumstances of leaving the childhood home; (d) focal patterns of distress, which included bereavement, concerns regarding the meaning of life, and thought processes (i.e., suicidal ideation); and (e) dysfunctional coping patterns such as alcohol abuse and elder abuse. England and Tripp-Reimer (2003) concluded that the diversity of issues identified by the participants represented awareness by adult children of their individual crises and their potential for ongoing caregiving of an aging parent. In addition, the frequency with which the participants reported on past and present experiences of crisis demonstrated the "nonlinear contextual nature of parent care and other human concerns" (England & Tripp-Reimer, 2003, p. 82).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…They cite higher levels of being sandwiched and feeling sandwiched across both Asians and Hispanics than across Caucasians and African Americans. England and Tripp-Reimer (2003), in a sample of 92 adult children caregivers who had experienced a crisis within the previous six months, studied their concerns and goals for caregiving and their recent crisis experiences. Most were women, first born, married, working, had provided care for six months or less, mostly for mothers, about four hours a day, involving Alzheimer's, and with most of the parents living in assisted living or nursing homes.…”
Section: Ethnic Differencesmentioning
confidence: 99%